Capital Market and Economic Growth in Nigeria: An Autoregressive Distributed Lag (ARDL) Bounds Testing Approach - Gwaison, Panan Danladi; Maimako, Livinus Nkuri; Mwolchet, Pokyes Shekara (International Journal of Finance Research, 2020)
The role of the capital market in the growth and development of any economy need not be over-emphasized. The capital market is a complex institution and mechanisms through which economic units desirous to invest their surplus fund, interact directly or through financial intermediaries with those who wish to procure funds for their businesses. The Nigerian capital market started operations in mid-1961 with eight stocks and equities; with about seven United Kingdom (UK) firms quoted on the Nigerian Stock Exchange (NSE) which had, at the same time, dual quotations on the London Stock Exchange. This study examined the impact of the capital market on economic growth in Nigeria from 1981 to 2018. The expo facto research design was adopted for this study. The time-series data for the study were sourced from CBN statistical bulletin. Autoregressive Distributed Lag (ARDL) was used with the aid of e-view 10 software. The ARDL Bounds test revealed the existence of a long-run relationship among the variables. The result revealed that market capitalization has positive and insignificant effects on economic growth both in the short and long run. There is unidirectional causality among the variables. The study recommended that regulatory authorities should restore confidence in the market by ensuring transparency and fair trading dealings and transactions in the market to enhance economic growth. There should be an improvement in the moribund market capitalization, by encouraging more foreign investors to participate in the market, maintain a state of the art technology like automated trading and settlement practices, electronic fund clearance, and eliminate physical transfer of shares.